The systematic review of the functionality of intellectual property rights in Indonesia. Issue 2 (30th September 2020) - Ariyesti, Fitri Rini; Ghufran, Muhammad; Ali, Sumran; Mardawani,
Abstract : This study focuses on the functionality of intellectual property right in Indonesia in both legislative and administrative functions. For this purpose, we considered three main kinds of intellectual property rights (IPRs) such as trademark, patent and copyright which are vital components for development of any country. After carefully review the three type legislatively and administratively we found that trademark legislation could be reconsidered for facilitation of Indonesian such as legislation of 21 A and B 2016, which explain about protection of famous international trademark but 74 (1) 2016 legislation only allow to use the international trademark for three successive years after registration. If they are failing to renew the registration someone can use these trademarks without the permission of parent company, legally and Indonesian government will also protect them. Administratively, in Indonesia, IPRs compliance frameworks leading to loss of trust among businesses and other parties involved in innovation and inventions because of restricted risk capital; poor investor and research development networks. In addition that, National legislation related to IPRs with its kinds has been found incomplete and not sufficient to cover all the aspects to meet the international standard such as recognition of IPRs on international level, Criminal and civil law implementation and border protection system.